Design and field tests of a deck-extension bridge with small box girder - Junqing Xue; Bruno Briseghella; Jianhui Lin; Fuyun Huang; Baochun Chen (Journal of Traffic and Transportation Engineering (English ed. Online), 2018)
A jointless bridge could fundamentally eliminate vulnerable deck joints, thereby meeting the need for sustainable development of bridges, especially for an expressway with high-speed traffic. In this paper, one jointless bridge (deck-extension bridge) with a small box girder in an expressway was chosen as a case study to examine the structural design, construction and field test. The field tests of the bridge indicated that the designed and constructed structures can satisfy the requirement for service performance of the deck-extension bridge. Some key technologies, such as the position of longitudinal reinforcements in the superstructure-approach slab connections and the arrangement of the sliding material layers, were introduced. The longitudinal thermal movement of the superstructure in the deck-extension bridge with a small box girder could be predicted accurately by using the average temperature of the cross section of a small box girder. The finite element model, built by using the MIDAS program, was used to analyze the temperature distribution on the cross section of a small box girder, the accuracy of which could be verified by comparing with the measured values. The maximum longitudinal thermal movement of the superstructure in deck-extension bridges with a small box girder under historically extreme temperature conditions was predicted. Keywords: Jointless bridge, Deck-extension bridge, Small box girder, Longitudinal thermal movement, Temperature distribution, Average temperature